Polymer electrolyte matrix, polymer electrolyte and method for producing the same, battery electrode sheet, and secondary battery
Patent Information
- Application Number
- CN202210413438.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-04-19
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2042-04-19
AI Technical Summary
[0003]目前,固态电解质的机械性能主要通过加入无机填料来改善,然而无机填料的加入量过多时,容易发生相不连续及产生稀释效果,使离子电导率降低;固态电解质的导电性能主要通过改变聚合物的结构进行提升,比如以聚甲基丙烯酸酯为主链、以聚醚链段为侧链构建接枝聚合物等,该方法通过聚合物玻璃化转变温度(Tg)的降低使聚合物结晶度降低,进而提高离子电导率,但该过程会破坏聚合物的结晶结构,不可避免地会降低聚合物电解质的机械性能
[0019] The method for preparing the polymer electrolyte matrix provided in this application is simple to operate and conducive to industrial production.
Smart Images

Figure CN116948151B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of secondary batteries, specifically to a polymer electrolyte matrix, a polymer electrolyte and its preparation method, battery electrodes, and a secondary battery. Background Technology
[0002] With the miniaturization, thinning, and lightening of electronic products, and the ever-increasing capacity demands of energy storage devices, improving the conductivity and mechanical properties of batteries has become a current research hotspot. Electrolytes are a crucial component of batteries, and solid polymer electrolytes, due to their high safety, high stability, and strong plasticity, exhibit adaptability advantages in battery shape design and assembly.
[0003] Currently, the mechanical properties of solid electrolytes are mainly improved by adding inorganic fillers. However, excessive addition of inorganic fillers can easily lead to phase discontinuity and dilution, resulting in a decrease in ionic conductivity. The electrical conductivity of solid electrolytes is primarily improved by altering the polymer structure, such as constructing graft polymers with polymethyl methacrylate as the main chain and polyether segments as side chains. This method utilizes the polymer's glass transition temperature (T0). g The reduction in conductivity decreases the crystallinity of the polymer, thereby increasing ionic conductivity. However, this process disrupts the polymer's crystalline structure, inevitably reducing the mechanical properties of the polymer electrolyte. Therefore, existing solid polymer electrolytes struggle to possess both excellent conductivity and mechanical properties, limiting their application in batteries. Summary of the Invention
[0004] In view of this, this application provides a polymer electrolyte matrix with a structure in which the crystallization region is controllable, that is, the polymer electrolyte matrix has a high degree of crystallinity in the short-range space and a low degree of crystallinity in the long-range space, which enables the polymer electrolyte to have both excellent electrical conductivity and mechanical properties.
[0005] Specifically, in a first aspect, this application provides a polymer electrolyte matrix comprising a polymer as shown in formula (1). (1) In equation (1), the structure of A1 is shown in equation (1-1), the structure of A2 is shown in equation (1-2), and the structure of A3 is shown in equation (1-3) or equation (1-4); 0 < k < 1; (1-1) (1-2) (1-3) (1-4) In formulas (1-1), (1-2), (1-3), and (1-4), R1, R2, R3, R4, R5, R6, R7, and R8 are independently selected from H or alkyl groups; m1, m2, m3, m4, n1, n2, n3, and n4 are independently selected from integers from 1 to 100. Indicates the connection bit.
[0006] In the polymer electrolyte matrix of this application, the structural units of the polymer backbone have similar conjugated structures, and the polymer side chains are flexible polyether segments. Lithium ions can migrate by complexing with the ether oxygen functional groups on the polyether segments. The similar conjugated structures A1, A2, and A3 give the polymer a structure with controllable crystallinity. In the short-range space, the backbone and side chains aggregate and form a crystalline structure through physical cross-linking, giving the short-range segments high crystallinity and ensuring the mechanical strength of the polymer electrolyte matrix. In the long-range space, since the backbone structure is a random segment, it does not aggregate and has an amorphous structure. The long-range segments have low crystallinity, ensuring the elasticity and toughness of the polymer electrolyte matrix. Moreover, the conjugated structure of the backbone can improve the complexation strength between lithium ions and polyether side chains, which helps lithium ion migration and ensures that the polymer electrolyte matrix has high ionic conductivity. Thus, the polymer electrolyte matrix has both excellent electrical and mechanical properties.
[0007] Optionally, the polymer is as shown in formulas (1-5). (1-5).
[0008] Optionally, the polymer is as shown in formulas (1-6). (1-6).
[0009] In formulas (1-5) and (1-6), R1, R2, R3, R4, R5, R6, R7, and R8 are independently selected from H or alkyl groups; m1, m2, m3, m4, n1, n2, n3, and n4 are independently selected from integers from 1 to 100, where 0 < k < 1. Indicates the connection bit.
[0010] Optional, 0.5 < k < 1.
[0011] Optional, 3≤k / (1-k)≤5.
[0012] Optionally, the polymer has a weight-average molecular weight of 1×10⁻⁶. 5 g / mol ~ 2 × 10 6 g / mol.
[0013] Optionally, the glass transition temperature T of the polymer g The temperature range is 15℃ to 25℃.
[0014] The polymer electrolyte matrix provided in the first aspect of this application has the advantages of high ionic conductivity, good thermal stability, high mechanical strength, high elasticity, high toughness, and high interfacial stability. Its application in batteries is beneficial to improving the conductivity and mechanical properties of batteries.
[0015] Secondly, this application provides a method for preparing the above-mentioned polymer electrolyte matrix, comprising the following steps: The first conjugated monomer, the second conjugated monomer, and the third conjugated monomer are mixed and polymerized to obtain the polymer electrolyte matrix; the first conjugated monomer includes a halonaphthyl diamine ether as shown in formula (2-1); the second conjugated monomer includes a halobispyrrole vinyl ether as shown in formula (2-2); and the third conjugated monomer includes a halobispyrrole ether as shown in formula (2-3) or a halopyrrolopyrrole ether as shown in formula (2-4). (2-1) (2-2) (2-3) (2-4) In formulas (2-1), (2-2), (2-3), and (2-4), X is a halogen atom, R1, R2, R3, R4, R5, R6, R7, and R8 are independently selected from H or alkyl groups; m1, m2, m3, m4, n1, n2, n3, and n4 are independently selected from integers from 1 to 100.
[0016] Optionally, mixing the first conjugated monomer, the second conjugated monomer, and the third conjugated monomer includes: The first conjugated monomer, the second conjugated monomer, and the third conjugated monomer are mixed in a molar ratio of 1:k:(1-k), where 0 < k < 1.
[0017] Optionally, the reaction temperature of the polymerization reaction is 100℃~150℃.
[0018] Optionally, the reaction time of the polymerization reaction is 4h to 24h.
[0019] The method for preparing the polymer electrolyte matrix provided in this application is simple to operate and conducive to industrial production.
[0020] Thirdly, this application provides a polymer electrolyte, including the polymer electrolyte matrix described in the first aspect of this application and a lithium salt dispersed in the polymer electrolyte matrix.
[0021] Optionally, the ratio of the number of lithium ions in the lithium salt to the number of oxygen atoms in the polymer electrolyte matrix is 1:(6~40).
[0022] Optionally, the polymer electrolyte may further include an inorganic filler.
[0023] Optionally, the inorganic filler includes one or more of LiAg4I5, Li3N, SiO2, Al2O3, MgO, ZrO2, TiO2, LiNbO3, BaTiO3, PbTiO3, montmorillonite, and molecular sieves.
[0024] Optionally, the particle size of the inorganic filler is 1 nm to 100 nm.
[0025] Optionally, the mass ratio of the inorganic filler to the polymer electrolyte matrix is 1:(14~30).
[0026] Optionally, the polymer electrolyte may also include a plasticizer.
[0027] Optionally, the plasticizer includes one or more of ethylene carbonate, propylene carbonate, and vinylene carbonate.
[0028] Optionally, the mass ratio of the plasticizer to the polymer electrolyte matrix is 1:(1~1.8).
[0029] Optionally, the lithium salt includes one or more of lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), lithium hexafluorosilicate (LiSiF6), lithium tetraphenylborate (LiB(C6H5)4), lithium chloride (LiCl), lithium bromide (LiBr), lithium chloroaluminate (LiAlCl4), lithium fluorocarbon sulfonate (LiC(SO2CF3)3), LiCH3SO3, LiN(SO2CF3)2, and LiN(SO2C2F5)2.
[0030] Optionally, the polymer electrolyte has an ionic conductivity of 1×10⁻⁶. -6 S / cm ~ 1×10 -2 S / cm.
[0031] Optionally, the tensile strength of the polymer electrolyte is 0.2 MPa to 0.9 MPa.
[0032] Optionally, the crystallinity of the polymer electrolyte is 10% to 70%.
[0033] Optionally, the elongation at break of the polymer electrolyte is 100% to 200%.
[0034] Optionally, the strain recovery rate of the polymer electrolyte is 10% to 100%.
[0035] The polymer electrolyte provided in the third aspect of this application has good film-forming properties, stability and plasticity, which is beneficial for its application in secondary batteries.
[0036] Fourthly, this application provides a method for preparing the above-mentioned polymer electrolyte, comprising: contacting the polymer electrolyte matrix described in the first aspect with a lithium salt solution, and drying it to obtain the polymer electrolyte.
[0037] Fifthly, this application provides a battery electrode sheet, including a current collector and an electrode material disposed on the current collector, the electrode material including an electrode active material and a polymer electrolyte matrix as described in any one of claims 1-4.
[0038] Optionally, the mass ratio of the electrode active material to the polymer electrolyte matrix is 1:(0.8~2).
[0039] Optionally, the electrode active material includes one or more of LiFePO4, LiMnO2, LiNiO2, LiCoO2, LiVPO4F, LiFeO2, and ternary cathode active materials.
[0040] The composite cathode provided in the fifth aspect of this application has excellent structural stability, thermal stability and cycling capability.
[0041] In a sixth aspect, this application provides a secondary battery, wherein the lithium-ion battery includes a polymer electrolyte matrix as described in the first aspect of this application; or the lithium-ion battery includes a polymer electrolyte as described in the third aspect of this application; or the lithium-ion battery includes a polymer electrolyte composite positive electrode as described in the fourth aspect of this application.
[0042] Optionally, the secondary battery includes a positive electrode, a negative electrode, and an electrolyte located between the positive electrode and the negative electrode, the electrolyte including a polymer electrolyte as described in the third aspect of this application.
[0043] In a seventh aspect, this application provides an electronic device comprising a secondary battery as described in the sixth aspect. Attached Figure Description
[0044] Figure 1 This is a schematic diagram of the structure of a secondary battery provided in an embodiment of this application. Detailed Implementation
[0045] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of this application.
[0046] Solid polymer electrolytes (SPEs) possess high safety, stability, and ease of molding and processing, facilitating battery shape design and assembly, and adapting to the miniaturization, thinning, and lightweight development requirements of electronic products. Since the electrode materials undergo continuous volume changes during charge-discharge cycles, the electrolyte requires a certain mechanical strength to withstand these changes. However, a current problem with polymer electrolytes is that mechanical properties and ionic conductivity cannot be simultaneously achieved. Some solid polymer electrolytes, even with ideal mechanical strength, exhibit very low ionic conductivity, which is detrimental to the battery's rate performance. To address the current problem of the inability to simultaneously achieve both mechanical strength and ionic conductivity in polymer electrolytes, this application provides a polymer electrolyte matrix comprising a polymer as shown in formula (1). (1), where 0 < k < 1. In this application, the polymer electrolyte matrix includes a first structural unit. Second structural unit The first structural unit consists of A1 and A2. The structural formula of A1 is shown in formula (1-1), and the structural formula of A2 is shown in formula (1-2). The second structural unit consists of A1 and A3. The structural formula of A3 is shown in formula (1-3) or formula (1-4). (1-1) (1-2) (1-3) (1-4) Wherein, R1, R2, R3, R4, R5, R6, R7, and R8 are independently selected from H or alkyl groups, and the alkyl group can be a C1-10 alkyl group, such as CH3; m1, m2, m3, m4, n1, n2, n3, and n4 are independently selected from integers from 1 to 100. Indicates the connection bit.
[0047] In this application, A1, A2, and A3 have similar conjugated structures, which is conducive to the aggregation of polymer segments in short-range space. The short-range segments cross-link through physical hydrogen bonds to form a crystalline structure. The crystallinity will not be destroyed during the stretching and compression of the polymer, thus ensuring that the polymer has high mechanical strength. When A1, A2, and A3 form a polymer with the structure of formula (1), the polymer segments are amorphous in long-range space. This structure is conducive to dissipating external stress to respond to strain, suppressing the destruction of the short-range crystalline structure and causing permanent deformation of the material, thereby improving the recovery performance of the polymer after deformation, regulating the deformation amplitude of the polymer during stretching and compression, suppressing the fracture deformation of the material, and giving the polymer electrolyte matrix good mechanical properties. Moreover, this conjugated structure is conducive to the migration of lithium ions. The side chains of the polymer are all flexible polyether segments. The flexible polyether segments contain ether oxygen functional groups that can complex lithium ions. The conjugated structure of the main chain can increase the electron cloud density on the polyether side chains, which is conducive to improving the binding strength between lithium ions and flexible segments, promoting the migration of lithium ions, and giving the polymer electrolyte matrix high ionic conductivity.
[0048] In some embodiments of this application, the polymer electrolyte matrix is as shown in formulas (1-5). (1-5).
[0049] In some embodiments of this application, the polymer electrolyte matrix is as shown in formulas (1-6). (1-6).
[0050] In formulas (1-5) and (1-6), R1, R2, R3, R4, R5, R6, R7, and R8 are independently selected from H or alkyl groups; m1, m2, m3, m4, n1, n2, n3, and n4 are independently selected from integers from 1 to 100, where 0 < k < 1. This indicates a link site, which can specifically be a link site connected to a capping group.
[0051] In this embodiment, k and (1-k) represent the molar ratio of the first structural unit to the second structural unit, where 0 < k < 1; in some embodiments, 0.5 < k < 1, meaning the proportion of the first structural unit is greater than that of the second structural unit. The specific value of k can be, but is not limited to, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, or 0.95. The main chain structure of the first structural unit is more flexible, and when its proportion is higher, the microcrystallineity of the polymer electrolyte matrix is more controllable, thereby ensuring that the polymer electrolyte matrix has good mechanical properties and ionic conductivity. In some embodiments of this application, the ratio of k to (1-k) is greater than or equal to 3 and less than or equal to 5, i.e., 3≤k / (1-k)≤5. When the molar ratio of the first structural unit to the second structural unit is controlled at 3~5, the short-range segments in the polymer electrolyte matrix are more likely to undergo physical cross-linking to form a crystalline structure, and the long-range segments have low crystallinity, which is conducive to forming a stable crystalline region controllable structure and improving the mechanical properties and ionic conductivity of the polymer electrolyte.
[0052] In this embodiment, the polyether segment of the polymer electrolyte matrix side chain can be one or more of polyethylene oxide (PEO), polypropylene oxide (PPO), and a copolymer of propylene oxide and ethylene oxide (PEPO). In some embodiments, R1, R2, R3, R4, R5, R6, R7, and R8 are H, meaning all polyether segments are PEO; in some embodiments, R1, R2, R3, R4, R5, R6, R7, and R8 are CH3, meaning all polyether segments are PPO; and in other embodiments, R1, R2, R3, R4, R5, R6, R7, and R8 are independently selected from H and CH3, meaning the polyether segments include both PEO and PPO.
[0053] In this application, the degree of polymerization of the polyether segments is 1 to 100, i.e., m1, m2, m3, m4, n1, n2, n3, and n4 are independently selected from integers from 1 to 100. In some embodiments of this application, m1, m2, m3, m4, n1, n2, n3, and n4 are independently selected from integers from 3 to 60. In some embodiments, the degree of polymerization of the polyether segments is 1 to 4, and the polyether segments are short chains; in some embodiments, the degree of polymerization of the polyether segments is 5 to 9, and the polyether segments are medium to long chains; in some embodiments, the degree of polymerization of the polyether segments is greater than 10, and the polyether segments are long chains. In some embodiments of this application, m1, m2, m3, m4, n1, n2, n3, and n4 are independently selected from integers from 3 to 20. The degree of polymerization of the polyether segment can be, but is not limited to, 3, 4, 5, 8, 10, 12, 15, 18, or 20. Due to the combined effects of electron-donating density and steric hindrance, when the degree of polymerization of the polyether segment is between 3 and 20, the lithium ion transport rate in the polymer electrolyte matrix is relatively high, which is beneficial to improving the ionic conductivity of the polymer electrolyte matrix.
[0054] In this embodiment, the polymer can be capped using a chemically acceptable capping agent. Specifically, in one embodiment, the capping group includes a phenyl group, in which case the polymer structure is shown in formula (2-5) or formula (2-6): (2-5), (2-6).
[0055] In some embodiments of this application, the weight-average molecular weight of the polymer is 1 × 10⁻⁶. 5 g / mol ~ 2 × 10 6 Controlling the weight-average molecular weight of the polymer (g / mol) is beneficial for improving the ionic conductivity of the polymer electrolyte matrix, enabling lithium ions to achieve higher levels of room-temperature ionic conductivity and transport number in the polymer electrolyte. The specific weight-average molecular weight of the polymer can be, but is not limited to, 1 × 10⁻⁶ g / mol. 5 g / mol, 2×10 5 g / mol, 3×10 5 g / mol, 6×10 5 g / mol, 8×10 5 g / mol, 1×10 6 g / mol, 1.5×10 6 g / mol, 1.8×10 6 g / mol, 2×10 6 g / mol. In some embodiments of this application, the glass transition temperature T of the polymer is... g The glass transition temperature (T) of the polymer is 15℃~25℃. g Specifically, the temperatures can be, but are not limited to, 15℃, 17℃, 19℃, 20℃, 22℃, 24℃, or 25℃.
[0056] The polymer electrolyte matrix provided in this application has a structure with controllable crystallization regions. This structure gives the polymer electrolyte matrix advantages such as high mechanical strength, high elasticity, and high toughness, which is beneficial for resisting electrode volume changes and extending battery life. The physically cross-linked crystal structure of this polymer electrolyte matrix in short-range space is not limited by the glass transition temperature. The ionic conductivity of the polymer electrolyte matrix can be further increased by lowering the glass transition temperature of the polymer without affecting the polymer structure, avoiding the problem of decreased mechanical properties caused by polymer structure changes, thus giving the polymer electrolyte matrix good thermal stability. Moreover, the randomness of the polymer backbone structure prevents polymer aggregation and results in low crystallinity in long-range space, which is beneficial for lithium ion migration and further improves the ionic conductivity of the polymer electrolyte matrix.
[0057] This application also provides a method for preparing the above-mentioned polymer electrolyte matrix, including the following steps: The first conjugated monomer, the second conjugated monomer, and the third conjugated monomer are mixed and polymerized to obtain a polymer electrolyte matrix.
[0058] In this application, the first conjugated monomer includes a halonaphthyl diamino ether as shown in formula (2-1); the second conjugated monomer includes a halobispyrrole vinyl ether as shown in formula (2-2); and the third conjugated monomer includes a halobispyrrole ether as shown in formula (2-3) or a halopyrrolopyrrole ether as shown in formula (2-4).
[0059] (2-1) (2-2) (2-3) (2-4) In formulas (2-1), (2-2), (2-3), and (2-4), X is a halogen atom, R1, R2, R3, R4, R5, R6, R7, and R8 are independently selected from H or alkyl groups; m1, m2, m3, m4, n1, n2, n3, and n4 are independently selected from integers from 1 to 100.
[0060] In the embodiments of this application, X in formulas (2-1), (2-2), (2-3), and (2-4) is a halogen atom, which can specifically be F, Cl, Br, or I. In some embodiments, X is Br. The brominated conjugated monomer raw materials are readily available, which helps to reduce production costs.
[0061] In the embodiments of this application, in the polymer described by formula (1) above, the first structural unit The second structural unit is derived from the first conjugated monomer shown in formula (2-1) and the second conjugated monomer shown in formula (2-2). The first conjugated monomer is derived from formula (2-1) and the third conjugated monomer is derived from formula (2-3) or formula (2-4). In embodiments of this application, the first conjugated monomer, the second conjugated monomer, and the third conjugated monomer are mixed in a molar ratio of 1:k:(1-k), where 0 < k < 1. In some embodiments, 0.5 < k < 1. In some embodiments, the first conjugated monomer, the second conjugated monomer, and the third conjugated monomer are mixed in a molar ratio of (4~6):(3~5):1.
[0062] In the embodiments of this application, the first conjugated monomer shown in formula (2-1) can be obtained by reacting a compound as shown in formula (2-7) with a polyether.
[0063] (2-7) In equation (2-7), X is a halogen atom, which can be F, Cl, Br, or I.
[0064] In this application, the polymerization reaction of mixing the first conjugated monomer, the second conjugated monomer, and the third conjugated monomer specifically includes: heating the mixture of the first conjugated monomer, the second conjugated monomer, and the third conjugated monomer in an organic solvent to undergo a polymerization reaction, forming a polymer. In some embodiments of this application, the organic solvent includes chlorobenzene. In some embodiments of this application, the polymerization reaction temperature is 100℃~150℃, and the specific polymerization reaction temperature may be, but is not limited to, 100℃, 110℃, 120℃, 130℃, 140℃, or 150℃. In some embodiments of this application, the polymerization reaction time is 4h~24h, and the specific polymerization reaction time may be, but is not limited to, 4h, 8h, 10h, 15h, 20h, or 24h.
[0065] This application also provides a polymer electrolyte, comprising the above-described polymer electrolyte matrix and a lithium salt dispersed in the polymer electrolyte matrix.
[0066] In this application, the lithium salt may be one or more of lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), lithium hexafluorosilicate (LiSiF6), lithium tetraphenylborate (LiB(C6H5)4), lithium chloride (LiCl), lithium bromide (LiBr), lithium chloroaluminate (LiAlCl4), and lithium fluorocarbon sulfonate (LiC(SO2CF3)3), LiCH3SO3, LiN(SO2CF3)2, and LiN(SO2C2F5)2. In some embodiments, when the lithium salt includes one or more of LiN(SO2C2F5)2 or LiPF6, the polymer electrolyte has a high room temperature ionic conductivity.
[0067] In some embodiments of this application, the ratio of the number of lithium ions in the lithium salt to the number of oxygen atoms in the polymer electrolyte matrix is 1:(6~40). This ratio can specifically be, but is not limited to, 1:6, 1:8, 1:10, 1:12, 1:15, 1:20, 1:25, 1:30, 1:35, or 1:40. In some embodiments of this application, the ratio of the number of lithium ions in the lithium salt to the number of oxygen atoms in the polymer electrolyte matrix is 1:(8~10). Controlling this ratio within the above range is beneficial for achieving a moderate carrier density and a low impedance value in the electrolyte, thereby enabling the polymer electrolyte to achieve a higher ionic conductivity.
[0068] In some embodiments of this application, the polymer electrolyte further includes inorganic fillers, which include one or more of LiAg4I5, Li3N, SiO2, Al2O3, MgO, ZrO2, TiO2, LiNbO3, BaTiO3, PbTiO3, montmorillonite, and molecular sieves. The particle size of the inorganic fillers is 1 nm to 100 nm. In some embodiments of this application, the mass ratio of the inorganic filler to the polymer electrolyte matrix is 1:(14~30). The specific mass ratio of the inorganic filler to the polymer electrolyte matrix can be, but is not limited to, 1:14, 1:15, 1:18, 1:20, 1:25, or 1:30. Adding an appropriate amount of inorganic filler to the polymer electrolyte can improve the mechanical properties of the polymer electrolyte, while the polymer electrolyte still maintains good ionic conductivity and stability.
[0069] In some embodiments of this application, the polymer electrolyte further includes a plasticizer, which includes one or more of ethylene carbonate, propylene carbonate, and vinylene carbonate. In some embodiments of this application, the mass ratio of the plasticizer to the polymer electrolyte matrix is 1:(1~1.8). The specific mass ratio of the plasticizer to the polymer electrolyte matrix may be, but is not limited to, 1:1, 1:1.2, 1:1.4, 1:1.6, or 1:1.8. Adding an appropriate amount of plasticizer to the polymer electrolyte can improve the ionic conductivity of the polymer electrolyte, while the polymer electrolyte still possesses good mechanical strength and stability.
[0070] In some embodiments of this application, the polymer electrolyte comprises the following components in weight percentages: 35wt% to 45wt% polymer electrolyte matrix, 25wt% to 35wt% lithium salt, 1.5wt% to 2.5wt% inorganic filler, and 25wt% to 35wt% plasticizer.
[0071] In this embodiment, the ionic conductivity of the polymer electrolyte is 1×10⁻⁶. -6 S / cm ~ 1×10 -2 S / cm, where the ionic conductivity of the polymer electrolyte refers to the ionic conductivity of the polymer electrolyte at 25°C. In some embodiments, the ionic conductivity of the polymer electrolyte is 1.4 × 10⁻⁶. -4 S / cm ~ 1.1×10 -3S / cm. In some embodiments of this application, the crystallinity of the polymer electrolyte is 10%~70%, and in some embodiments, the crystallinity is 30%~40%. In some embodiments of this application, the polymer electrolyte is a film-like solid electrolyte, and the elongation at break of the polymer electrolyte is 100%~200%, wherein the elongation at break refers to the ratio of the elongation length before and after stretching to the original length before stretching when the polymer electrolyte film is stretched to break; in some embodiments, the elongation at break is 120%~140%. In some embodiments of this application, the tensile strength of the polymer electrolyte is 0.2MPa~0.9MPa, and the tensile strength of the polymer electrolyte refers to the maximum nominal tensile stress that the polymer electrolyte can withstand before breaking; in some embodiments, the tensile strength is 0.5MPa~0.6MPa. In embodiments of this application, the strain recovery rate of the polymer electrolyte is 10%~100%, and the strain recovery rate of the polymer electrolyte refers to the percentage of deformation recovered after the stress disappears from the maximum deformation under stress; in some embodiments, the strain recovery rate of the polymer electrolyte is 70%~80%.
[0072] In some embodiments of this application, the polymer electrolyte can be prepared by the following steps: The polymer electrolyte matrix is contacted with a lithium salt solution to adsorb lithium salt, and then dried to obtain the polymer electrolyte.
[0073] In some embodiments of this application, the preparation of the polymer electrolyte further includes: before contacting the polymer electrolyte matrix with the lithium salt solution, mixing the polymer electrolyte matrix with an inorganic filler, heating and stirring, and then drying to form a doped film at a drying temperature of 100°C to 150°C; then contacting the doped film with the lithium salt solution to prepare the polymer electrolyte. In some embodiments of this application, the solvent of the lithium salt solution is an organic solvent, such as ethyl acetate, and the contact time between the polymer electrolyte matrix and the lithium salt solution is 1 hour to 36 hours. In some embodiments of this application, after contacting the polymer electrolyte matrix with the lithium salt solution to adsorb lithium salt and drying it at a temperature of 45°C to 75°C, a plasticizer is added to the polymer film, and after swelling for at least 2 hours, the polymer electrolyte is obtained.
[0074] The polymer electrolyte prepared by the method provided in this application has the advantages of good film-forming properties, good stability, and strong plasticity, which is beneficial for its application in batteries.
[0075] This application also provides a battery electrode, including a current collector and an electrode material disposed on the current collector. The electrode material includes an electrode active material and the aforementioned polymer electrolyte matrix. In this application, the battery electrode can be either a positive electrode or a negative electrode.
[0076] In some embodiments, the positive electrode sheet includes a current collector and a positive electrode material disposed on the current collector. The positive electrode current collector includes aluminum foil. This application does not impose any particular limitation on the positive electrode material, which may include a positive electrode active material, a binder, and a conductive agent. The positive electrode active material may be one or more of LiFePO4, LiMnO2, LiNiO2, LiCoO2, LiVPO4F, LiFeO2, and ternary positive electrode active materials.
[0077] In some embodiments, the negative electrode sheet includes a current collector and a negative electrode material disposed on the current collector. The negative electrode current collector includes copper foil. This application does not impose any particular limitation on the negative electrode material, which may include a negative electrode active material, a binder, and a conductive agent. The negative electrode active material may be one or more of natural graphite, artificial graphite, hard carbon, soft carbon, and lithium titanate.
[0078] The adhesive may be any adhesive known in the art, such as one or more of polyvinylidene fluoride, polytetrafluoroethylene, styrene-butadiene rubber, and polyacrylate. The conductive agent may be any conductive agent known in the art, such as one or more of graphite, carbon fiber, carbon black, metal powder, metal oxide, and fiber.
[0079] In some embodiments of this application, the polymer electrolyte matrix can replace all or part of the binder in the positive or negative electrode sheet. The polymer electrolyte matrix of this application has good ionic conductivity, which can effectively reduce the internal resistance of the battery electrode sheet. Furthermore, due to the good mechanical strength and elasticity of the polymer matrix, it can adapt to the volume changes of the battery electrode sheet during charging and discharging, suppress the shedding of electrode material, and improve the structural stability of the electrode sheet.
[0080] In some embodiments of this application, the battery electrode sheet can be prepared by the following steps: The electrode active material, conductive agent, polymer electrolyte matrix and solvent are mixed evenly, the mixture is poured onto a block of polytetrafluoroethylene, bonded into a block composite material, and then coated onto the positive electrode current collector. The mixture is then heated under vacuum to 120℃~170℃ to obtain the battery electrode sheet.
[0081] This application also provides a secondary battery, including the above-mentioned polymer electrolyte matrix; or including the above-mentioned polymer electrolyte; or including the above-mentioned battery electrode.
[0082] Please see Figure 1 , Figure 1This is a schematic diagram of the structure of a secondary battery provided in an embodiment of this application. The secondary battery includes a positive electrode 101, a negative electrode 103, and a polymer electrolyte 102 located between the positive electrode and the negative electrode. In this application, the secondary battery can be prepared using methods known in the art. For example, a solution containing a polymer electrolyte matrix can be coated onto the surface of the positive or negative electrode sheet, and a polymer electrolyte film can be formed by drying to remove the solvent. Then, the positive and negative electrode sheets coated with the polymer electrolyte are wound or stacked to form an electrode core, which is then placed in a battery casing, sealed, formed, sealed, and packaged. Alternatively, a polymer electrolyte film can be prepared first, then attached to the surface of the positive or negative electrode sheet, and the positive and negative electrode sheets can be wound or stacked to form an electrode core, which is then placed in a battery casing, sealed, formed, sealed, and packaged. Another method is to add a polymer electrolyte between the positive and negative electrode sheets with the polymer electrolyte provided in this application adhered to them, then wind or stack the positive and negative electrode sheets to form an electrode core, which is then placed in a battery casing, sealed, formed, sealed, and packaged. The added polymer includes the polymer electrolyte provided in this application, and may also include other polymer electrolytes and separator materials. The sealing and formation operations described above can be performed using methods known in the art.
[0083] The secondary battery provided in this application has good structural stability, electrochemical performance, safety performance, and long service life.
[0084] The implementation scheme of this application will be further explained below with several case studies.
[0085] Example 1 (1) Preparation of elastic polymer electrolyte membrane Provide a first monomer (bromonaphthyl diamino ether, NDIO, R1=R2=H, n1=m1=4) as shown in formula (A), a second monomer (bromobispyrrole vinyl ether, R3=R4=H, n2=m2=4) as shown in formula (B), and a third monomer (bromobispyrrole ether, R5=R6=H, n3=m3=4) as shown in formula (C).
[0086] Formula (A); Formula (B); Formula (C); The first, second, and third monomers were mixed in a molar ratio of 5:4:1. The resulting mixture was heated in chlorobenzene solvent to 120°C to undergo a polymerization reaction, producing a polymer with a weight-average molecular weight of 1.2 × 10⁻⁶. 5Add an appropriate amount of SiO2 with an average particle size of 14 nm to g / mol, heat to 120°C, and stir until uniformly mixed to obtain a prepolymer melt; pour the prepolymer melt onto a glass slide, heat to 120°C in a vacuum chamber overnight, remove the formed film from the glass slide, weigh it, immerse the film in an ethyl acetate solution of lithium salt for 24 hours, swell, and dry overnight in a vacuum chamber at 60°C to form the first film, weigh it to calculate the amount of lithium salt; transfer the first film to an argon-filled glove box to prevent the first film from absorbing moisture from the air, add propylene carbonate in the glove box, and after the first film swells for at least 2 hours and reaches equilibrium, obtain the polymer electrolyte membrane S1. The obtained polymer electrolyte membrane includes the following components in the following mass percentages: 36.2 wt% polymer, 31.2 wt% lithium salt, 2.3 wt% inorganic filler, and 30.3 wt% propylene carbonate.
[0087] (2) Preparation of elastic polymer electrolyte composite positive electrode Take 35wt% lithium iron phosphate (LiFePO4), 5wt% single-walled carbon nanotubes, 45wt% polymer electrolyte membrane S1 and N-methylpyrrolidone (NMP), mix them evenly, pour the mixture onto a block of polytetrafluoroethylene, heat it under vacuum to 150℃, and leave it overnight to obtain an elastic polymer electrolyte composite positive electrode C1.
[0088] Example 2 (1) Preparation of elastic polymer electrolyte membrane The first monomer (bromonaphthyl diamino ether, NDIO, R1=R2=H, n1=m1=9), the second monomer (bromobispyrrole vinyl ether, R3=R4=H, n2=m2=9) and the third monomer (bromobispyrrole ether, R5=R6=H, n3=m3=9) are provided.
[0089] The first, second, and third monomers were mixed in a molar ratio of 5:4:1. The resulting mixture was heated in chlorobenzene solvent to 120°C to undergo a polymerization reaction, producing a polymer with a weight-average molecular weight of 2.1 × 10⁻⁶. 5 g / mol; Add an appropriate amount of SiO2 with an average particle size of 14 nm, heat to 120 °C, stir until uniformly mixed to obtain a prepolymer melt; Pour the prepolymer melt onto a glass slide, heat to 120 °C in a vacuum chamber overnight, remove the generated film from the glass slide, weigh it, immerse the film in an ethyl acetate solution of lithium salt for 24 hours, after swelling, dry in a vacuum chamber at 60 °C overnight to form the first film, weigh it to calculate the amount of lithium salt; Transfer the first film to an argon-filled glove box to prevent the first film from absorbing moisture from the air, add propylene carbonate to the glove box, and after the first film swells for at least 2 hours and reaches equilibrium, obtain the polymer electrolyte membrane S2.
[0090] (2) Preparation of elastic polymer electrolyte composite positive electrode Take 35wt% lithium iron phosphate (LiFePO4), 5wt% single-walled carbon nanotubes, 45wt% polymer electrolyte membrane S2 and N-methylpyrrolidone (NMP), mix them evenly, pour the mixture onto a block of polytetrafluoroethylene, heat it under vacuum to 150℃, and leave it overnight to obtain an elastic polymer electrolyte composite positive electrode C2.
[0091] Example 3 (1) Preparation of elastic polymer electrolyte membrane The first monomer (bromonaphthyl diamino ether, NDIO, R1=R2=H, n1=m1=12), the second monomer (bromobispyrrole vinyl ether, R3=R4=H, n2=m2=12) and the third monomer (bromobispyrrole ether, R5=R6=H, n3=m3=12) are provided.
[0092] The first, second, and third monomers were mixed in a molar ratio of 5:4:1. The resulting mixture was heated in chlorobenzene solvent to 120°C to undergo a polymerization reaction, producing a polymer with a weight-average molecular weight of 3.4 × 10⁻⁶. 5 g / mol; Add an appropriate amount of SiO2 with an average particle size of 14 nm, heat to 120 °C, stir until uniformly mixed to obtain a prepolymer melt; Pour the prepolymer melt onto a glass slide, heat to 120 °C in a vacuum chamber overnight, remove the generated film from the glass slide, weigh it, immerse the film in an ethyl acetate solution of lithium salt for 24 hours, after swelling, dry overnight in a vacuum chamber at 60 °C to form the first film, weigh it to calculate the amount of lithium salt; Transfer the first film to an argon-filled glove box to prevent the first film from absorbing moisture from the air, add propylene carbonate to the glove box, and after the first film swells for at least 2 hours and reaches equilibrium, obtain the polymer electrolyte membrane S3.
[0093] (2) Preparation of elastic polymer electrolyte composite positive electrode Take 35wt% lithium iron phosphate (LiFePO4), 5wt% single-walled carbon nanotubes, 45wt% polymer electrolyte membrane S3 and N-methylpyrrolidone (NMP), mix them evenly, pour the mixture onto a block of polytetrafluoroethylene, heat it under vacuum to 150℃, and leave it overnight to obtain an elastic polymer electrolyte composite positive electrode C3.
[0094] Example 4 (1) Preparation of elastic polymer electrolyte membrane The first monomer (bromonaphthyl diamino ether, NDIO, R1=R2=CH3, n1=m1=4), the second monomer (bromobispyrrole vinyl ether, R3=R4=CH3, n2=m2=4) and the third monomer (bromobispyrrole ether, R5=R6=CH3, n3=m3=4) are provided.
[0095] The first, second, and third monomers were mixed in a molar ratio of 5:4:1. The resulting mixture was heated in chlorobenzene solvent to 120°C to undergo a polymerization reaction, producing a polymer with a weight-average molecular weight of 1.9 × 10⁻⁶. 5 g / mol; Add an appropriate amount of SiO2 with an average particle size of 14 nm, heat to 120 °C, and stir until uniformly mixed to obtain a prepolymer melt; Pour the prepolymer melt onto a glass slide, heat to 120 °C in a vacuum chamber overnight, remove the generated film from the glass slide, weigh it, immerse the film in an ethyl acetate solution of lithium salt for 24 hours, after swelling, dry in a vacuum chamber at 60 °C overnight to form the first film, weigh it to calculate the amount of lithium salt; Transfer the first film to an argon-filled glove box to prevent the first film from absorbing moisture from the air, add propylene carbonate in the glove box, and after the first film swells for at least 2 hours and reaches equilibrium, obtain the polymer electrolyte membrane S4.
[0096] (2) Preparation of elastic polymer electrolyte composite positive electrode Take 35wt% lithium iron phosphate (LiFePO4), 5wt% single-walled carbon nanotubes, 45wt% polymer electrolyte membrane S4 and N-methylpyrrolidone (NMP), mix them evenly, pour the mixture onto a block of polytetrafluoroethylene, heat it under vacuum to 150℃, and leave it overnight to obtain the elastic polymer electrolyte composite cathode C4.
[0097] Example 5 (1) Preparation of elastic polymer electrolyte membrane The first monomer (bromonaphthyl diamino ether, NDIO, R1=R2=CH3, n1=m1=6), the second monomer (bromobispyrrole vinyl ether, R3=R4=CH3, n2=m2=6) and the third monomer (bromobispyrrole ether, R5=R6=CH3, n3=m3=6) are provided.
[0098] The first, second, and third monomers were mixed in a molar ratio of 5:4:1. The resulting mixture was heated in chlorobenzene solvent to 120°C to undergo a polymerization reaction, producing a polymer with a weight-average molecular weight of 2.5 × 10⁻⁶. 5g / mol; Add an appropriate amount of SiO2 with an average particle size of 14 nm, heat to 120 °C, and stir until uniformly mixed to obtain a prepolymer melt; Pour the prepolymer melt onto a glass slide, heat to 120 °C in a vacuum chamber overnight, remove the generated film from the glass slide, weigh it, immerse the film in an ethyl acetate solution of lithium salt for 24 hours, after swelling, dry in a vacuum chamber at 60 °C overnight to form the first film, weigh it to calculate the amount of lithium salt; Transfer the first film to an argon-filled glove box to prevent the first film from absorbing moisture from the air, add propylene carbonate to the glove box, and after the first film swells for at least 2 hours and reaches equilibrium, obtain the polymer electrolyte membrane S5.
[0099] (2) Preparation of elastic polymer electrolyte composite positive electrode Take 35wt% lithium iron phosphate (LiFePO4), 5wt% single-walled carbon nanotubes, 45wt% polymer electrolyte membrane S5 and N-methylpyrrolidone (NMP), mix them evenly, pour the mixture onto a block of polytetrafluoroethylene, heat it under vacuum to 150℃, and leave it overnight to obtain an elastic polymer electrolyte composite positive electrode C5.
[0100] Example 6 (1) Preparation of elastic polymer electrolyte membrane The first monomer (bromonaphthyl diamino ether, NDIO, R1=R2=CH3, n1=m1=12), the second monomer (bromobispyrrole vinyl ether, R3=R4=CH3, n2=m2=12) and the third monomer (bromobispyrrole ether, R5=R6=CH3, n3=m3=12) are provided.
[0101] The first, second, and third monomers were mixed in a molar ratio of 5:4:1. The resulting mixture was heated in chlorobenzene solvent to 120°C to undergo a polymerization reaction, producing a polymer with a weight-average molecular weight of 3.9 × 10⁻⁶. 5 g / mol; Add an appropriate amount of SiO2 with an average particle size of 14 nm, heat to 120 °C, stir until uniformly mixed to obtain a prepolymer melt; Pour the prepolymer melt onto a glass slide, heat to 120 °C in a vacuum chamber overnight, remove the generated film from the glass slide, weigh it, immerse the film in an ethyl acetate solution of lithium salt for 24 hours, after swelling, dry in a vacuum chamber at 60 °C overnight to form the first film, weigh it to calculate the amount of lithium salt; Transfer the first film to an argon-filled glove box to prevent the first film from absorbing moisture from the air, add propylene carbonate in the glove box, and after the first film swells for at least 2 hours and reaches equilibrium, obtain the polymer electrolyte membrane S6.
[0102] (2) Preparation of elastic polymer electrolyte composite positive electrode Take 35wt% lithium iron phosphate (LiFePO4), 5wt% single-walled carbon nanotubes, 45wt% polymer electrolyte membrane S6 and N-methylpyrrolidone (NMP), mix them evenly, pour the mixture onto a block of polytetrafluoroethylene, heat it under vacuum to 150℃, and leave it overnight to obtain an elastic polymer electrolyte composite positive electrode C6.
[0103] Example 7 (1) Preparation of elastic polymer electrolyte membrane The product provides a first monomer (bromonaphthyl diamino ether, NDIO, R1=H, R2=CH3, n1=4, m1=12), a second monomer (bromobispyrrole vinyl ether, R3=H, R4=CH3, n2=4, m2=12) and a third monomer (bromobispyrrole ether, R5=H, R6=CH3, n3=4, m3=12).
[0104] The first, second, and third monomers were mixed in a molar ratio of 5:4:1. The resulting mixture was heated in chlorobenzene solvent to 120°C to undergo a polymerization reaction, producing a polymer with a weight-average molecular weight of 3.1 × 10⁻⁶. 5 g / mol; Add an appropriate amount of SiO2 with an average particle size of 14 nm, heat to 120 °C, stir until uniformly mixed to obtain a prepolymer melt; Pour the prepolymer melt onto a glass slide, heat to 120 °C in a vacuum chamber overnight, remove the generated film from the glass slide, weigh it, immerse the film in an ethyl acetate solution of lithium salt for 24 hours, after swelling, dry in a vacuum chamber at 60 °C overnight to form the first film, weigh it to calculate the amount of lithium salt; Transfer the first film to an argon-filled glove box to prevent the first film from absorbing moisture from the air, add propylene carbonate to the glove box, and after the first film swells for at least 2 hours and reaches equilibrium, obtain the polymer electrolyte membrane S7.
[0105] (2) Preparation of elastic polymer electrolyte composite positive electrode Take 35wt% lithium iron phosphate (LiFePO4), 5wt% single-walled carbon nanotubes, 45wt% polymer electrolyte membrane S7 and N-methylpyrrolidone (NMP), mix them evenly, pour the mixture onto a block of polytetrafluoroethylene, heat it under vacuum to 150℃, and leave it overnight to obtain the elastic polymer electrolyte composite cathode C7.
[0106] Example 8 (1) Preparation of elastic polymer electrolyte membrane Provided are a first monomer (bromonaphthyl diamino ether, NDIO, R1=R2=H, n1=m1=4), a second monomer (bromobispyrrole vinyl ether, R3=R4=H, n2=m2=4) and a third monomer (bromopyrrolopyrrole ether, R7=R8=H, n4=m4=4) as shown in formula (D).
[0107] Formula (D).
[0108] The first, second, and third monomers were mixed in a molar ratio of 5:4:1. The resulting mixture was heated in chlorobenzene solvent to 120°C to undergo a polymerization reaction, producing a polymer with a weight-average molecular weight of 6 × 10⁻⁶. 5 g / mol; Add an appropriate amount of SiO2 with an average particle size of 14 nm, heat to 120 °C, and stir until uniformly mixed to obtain a prepolymer melt; Pour the prepolymer melt onto a glass slide, heat to 120 °C in a vacuum chamber overnight, remove the generated film from the glass slide, weigh it, immerse the film in an ethyl acetate solution of lithium salt for 24 hours, after swelling, dry in a vacuum chamber at 60 °C overnight to form the first film, weigh it to calculate the amount of lithium salt; Transfer the first film to an argon-filled glove box to prevent the first film from absorbing moisture from the air, add propylene carbonate to the glove box, and after the first film swells for at least 2 hours and reaches equilibrium, obtain the polymer electrolyte membrane S8.
[0109] (2) Preparation of elastic polymer electrolyte composite positive electrode Take 35wt% lithium iron phosphate (LiFePO4), 5wt% single-walled carbon nanotubes, 45wt% polymer electrolyte membrane S8 and N-methylpyrrolidone (NMP), mix them evenly, pour the mixture onto a block of polytetrafluoroethylene, heat it under vacuum to 150℃, and leave it overnight to obtain an elastic polymer electrolyte composite positive electrode C8.
[0110] Example 9 (1) Preparation of elastic polymer electrolyte membrane The first monomer (bromonaphthyl diamino ether, NDIO, R1=R2=H, n1=m1=9), the second monomer (bromobispyrrole vinyl ether, R3=R4=H, n2=m2=9) and the third monomer (bromopyrrolopyrrole ether, R7=R8=H, n4=m4=9) are provided.
[0111] The first, second, and third monomers were mixed in a molar ratio of 5:4:1. The resulting mixture was heated in chlorobenzene solvent to 120°C to undergo a polymerization reaction, producing a polymer with a weight-average molecular weight of 1.1 × 10⁻⁶. 5g / mol; Add an appropriate amount of SiO2 with an average particle size of 14 nm, heat to 120 °C, and stir until uniformly mixed to obtain a prepolymer melt; Pour the prepolymer melt onto a glass slide, heat to 120 °C in a vacuum chamber overnight, remove the generated film from the glass slide, weigh it, immerse the film in an ethyl acetate solution of lithium salt for 24 hours, after swelling, dry in a vacuum chamber at 60 °C overnight to form the first film, weigh it to calculate the amount of lithium salt; Transfer the first film to an argon-filled glove box to prevent the first film from absorbing moisture from the air, add propylene carbonate in the glove box, and after the first film swells for at least 2 hours and reaches equilibrium, obtain the polymer electrolyte membrane S9.
[0112] (2) Preparation of elastic polymer electrolyte composite positive electrode Take 35wt% lithium iron phosphate (LiFePO4), 5wt% single-walled carbon nanotubes, 45wt% polymer electrolyte membrane S9 and N-methylpyrrolidone (NMP), mix them evenly, pour the mixture onto a block of polytetrafluoroethylene, heat it under vacuum to 150℃, and leave it overnight to obtain the elastic polymer electrolyte composite positive electrode C9.
[0113] Example 10 (1) Preparation of elastic polymer electrolyte membrane The first monomer (bromonaphthyl diamino ether, NDIO, R1=R2=H, n1=m1=12), the second monomer (bromobispyrrole vinyl ether, R3=R4=H, n2=m2=12) and the third monomer (bromopyrrolopyrrole ether, R7=R8=H, n4=m4=12) are provided.
[0114] The first, second, and third monomers were mixed in a molar ratio of 5:4:1. The resulting mixture was heated in chlorobenzene solvent to 120°C to undergo a polymerization reaction, producing a polymer with a weight-average molecular weight of 2.6 × 10⁻⁶. 5 g / mol; Add an appropriate amount of SiO2 with an average particle size of 14 nm, heat to 120 °C, and stir until uniformly mixed to obtain a prepolymer melt; Pour the prepolymer melt onto a glass slide, heat to 120 °C in a vacuum chamber overnight, remove the generated film from the glass slide, weigh it, immerse the film in an ethyl acetate solution of lithium salt for 24 hours, after swelling, dry in a vacuum chamber at 60 °C overnight to form the first film, weigh it to calculate the amount of lithium salt; Transfer the first film to an argon-filled glove box to prevent the first film from absorbing moisture from the air, add propylene carbonate to the glove box, and after the first film swells for at least 2 hours and reaches equilibrium, obtain the polymer electrolyte membrane S10.
[0115] (2) Preparation of elastic polymer electrolyte composite positive electrode Take 35wt% lithium iron phosphate (LiFePO4), 5wt% single-walled carbon nanotubes, 45wt% polymer electrolyte membrane S10 and N-methylpyrrolidone (NMP), mix them evenly, pour the mixture onto a block of polytetrafluoroethylene, heat it under vacuum to 150℃, and leave it overnight to obtain the elastic polymer electrolyte composite positive electrode C10.
[0116] Example 11 (1) Preparation of elastic polymer electrolyte membrane The first monomer (bromonaphthyl diamino ether, NDIO, R1=R2=CH3, n1=m1=4), the second monomer (bromobispyrrole vinyl ether, R3=R4=CH3, n2=m2=4) and the third monomer (bromopyrrolopyrrole ether, R7=R8=CH3, n4=m4=4) are provided.
[0117] The first, second, and third monomers were mixed in a molar ratio of 5:4:1. The resulting mixture was heated in chlorobenzene solvent to 120°C to undergo a polymerization reaction, producing a polymer with a weight-average molecular weight of 3.7 × 10⁻⁶. 5 g / mol; Add an appropriate amount of SiO2 with an average particle size of 14 nm, heat to 120 °C, and stir until uniformly mixed to obtain a prepolymer melt; Pour the prepolymer melt onto a glass slide, heat to 120 °C in a vacuum chamber overnight, remove the generated film from the glass slide, weigh it, immerse the film in an ethyl acetate solution of lithium salt for 24 hours, after swelling, dry in a vacuum chamber at 60 °C overnight to form the first film, weigh it to calculate the amount of lithium salt; Transfer the first film to an argon-filled glove box to prevent the first film from absorbing moisture from the air, add propylene carbonate to the glove box, and after the first film swells for at least 2 hours and reaches equilibrium, obtain the polymer electrolyte membrane S11.
[0118] (2) Preparation of elastic polymer electrolyte composite positive electrode Take 35wt% lithium iron phosphate (LiFePO4), 5wt% single-walled carbon nanotubes, 45wt% polymer electrolyte membrane S11 and N-methylpyrrolidone (NMP), mix them evenly, pour the mixture onto a block of polytetrafluoroethylene, heat it under vacuum to 150℃, and leave it overnight to obtain the elastic polymer electrolyte composite positive electrode C11.
[0119] Example 12 (1) Preparation of elastic polymer electrolyte membrane The first monomer (bromonaphthyl diamino ether, NDIO, R1=R2=CH3, n1=m1=9), the second monomer (bromobispyrrole vinyl ether, R3=R4=CH3, n2=m2=9) and the third monomer (bromopyrrolopyrrole ether, R7=R8=CH3, n4=m4=9) are provided.
[0120] The first, second, and third monomers were mixed in a molar ratio of 5:4:1. The resulting mixture was heated in chlorobenzene solvent to 120°C to undergo a polymerization reaction, producing a polymer with a weight-average molecular weight of 1.5 × 10⁻⁶. 5 g / mol; Add an appropriate amount of SiO2 with an average particle size of 14 nm, heat to 120 °C, and stir until uniformly mixed to obtain a prepolymer melt; Pour the prepolymer melt onto a glass slide, heat to 120 °C in a vacuum chamber overnight, remove the generated film from the glass slide, weigh it, immerse the film in an ethyl acetate solution of lithium salt for 24 hours, after swelling, dry in a vacuum chamber at 60 °C overnight to form the first film, weigh it to calculate the amount of lithium salt; Transfer the first film to an argon-filled glove box to prevent the first film from absorbing moisture from the air, add propylene carbonate to the glove box, and after the first film swells for at least 2 hours and reaches equilibrium, obtain the polymer electrolyte membrane S12.
[0121] (2) Preparation of elastic polymer electrolyte composite positive electrode Take 35 wt% lithium iron phosphate (LiFePO4), 5 wt% single-walled carbon nanotubes, 45 wt% polymer electrolyte membrane S12 and N-methylpyrrolidone (NMP), mix them evenly, pour the mixture onto a block of polytetrafluoroethylene, heat it under vacuum to 150°C, and leave it overnight to obtain the elastic polymer electrolyte composite cathode C12.
[0122] Example 13 (1) Preparation of elastic polymer electrolyte membrane The first monomer (bromonaphthyl diamino ether, NDIO, R1=R2=CH3, n1=m1=12), the second monomer (bromobispyrrole vinyl ether, R3=R4=CH3, n2=m2=12) and the third monomer (bromopyrrolopyrrole ether, R7=R8=CH3, n4=m4=12) are provided.
[0123] The first, second, and third monomers were mixed in a molar ratio of 5:4:1. The resulting mixture was heated in chlorobenzene solvent to 120°C to undergo a polymerization reaction, producing a polymer with a weight-average molecular weight of 2.7 × 10⁻⁶. 5g / mol; Add an appropriate amount of SiO2 with an average particle size of 14 nm, heat to 120 °C, stir until uniformly mixed to obtain a prepolymer melt; Pour the prepolymer melt onto a glass slide, heat to 120 °C in a vacuum chamber overnight, remove the generated film from the glass slide, weigh it, immerse the film in an ethyl acetate solution of lithium salt for 24 hours, after swelling, dry in a vacuum chamber at 60 °C overnight to form the first film, weigh it to calculate the amount of lithium salt; Transfer the first film to an argon-filled glove box to prevent the first film from absorbing moisture from the air, add propylene carbonate to the glove box, and after the first film swells for at least 2 hours and reaches equilibrium, obtain the polymer electrolyte membrane S13.
[0124] (2) Preparation of elastic polymer electrolyte composite positive electrode Take 35wt% lithium iron phosphate (LiFePO4), 5wt% single-walled carbon nanotubes, 45wt% polymer electrolyte membrane S13 and N-methylpyrrolidone (NMP), mix them evenly, pour the mixture onto a block of polytetrafluoroethylene, heat it under vacuum to 150℃, and leave it overnight to obtain the elastic polymer electrolyte composite positive electrode C13.
[0125] Example 14 (1) Preparation of elastic polymer electrolyte membrane The product provides a first monomer (bromonaphthyl diamino ether, NDIO, R1=H, R2=CH3, n1=4, m1=12), a second monomer (bromobispyrrole vinyl ether, R3=H, R4=CH3, n2=4, m2=12) and a third monomer (bromopyrrolopyrrole ether, R7=H, R8=CH3, n3=4, m3=12).
[0126] The first, second, and third monomers were mixed in a molar ratio of 5:4:1. The resulting mixture was heated in chlorobenzene solvent to 120°C to undergo a polymerization reaction, producing a polymer with a weight-average molecular weight of 3.8 × 10⁻⁶. 5 g / mol; Add an appropriate amount of SiO2 with an average particle size of 14 nm, heat to 120 °C, stir until uniformly mixed to obtain a prepolymer melt; Pour the prepolymer melt onto a glass slide, heat to 120 °C in a vacuum chamber overnight, remove the generated film from the glass slide, weigh it, immerse the film in an ethyl acetate solution of lithium salt for 24 hours, after swelling, dry overnight in a vacuum chamber at 60 °C to form the first film, weigh it to calculate the amount of lithium salt; Transfer the first film to an argon-filled glove box to prevent the first film from absorbing moisture from the air, add propylene carbonate in the glove box, and after the first film swells for at least 2 hours and reaches equilibrium, obtain the polymer electrolyte membrane S14.
[0127] (2) Preparation of elastic polymer electrolyte composite positive electrode Take 35 wt% lithium iron phosphate (LiFePO4), 5 wt% single-walled carbon nanotubes, 45 wt% polymer electrolyte membrane S14 and N-methylpyrrolidone (NMP), mix them evenly, pour the mixture onto a block of polytetrafluoroethylene, heat it under vacuum to 150°C, and leave it overnight to obtain the elastic polymer electrolyte composite positive electrode C14.
[0128] Example 15 (1) Preparation of elastic polymer electrolyte membrane The first monomer (bromonaphthyl diamino ether, NDIO, R1=R2=H, n1=m1=4), the second monomer (bromobispyrrole vinyl ether, R3=R4=H, n2=m2=4) and the third monomer (bromopyrrolopyrrole ether, R5=R6=H, n3=m3=4) are provided.
[0129] The first, second, and third monomers were mixed in a molar ratio of 5:1:4. The resulting mixture was heated in chlorobenzene solvent to 120°C to undergo a polymerization reaction, producing a polymer with a weight-average molecular weight of 1.4 × 10⁻⁶. 5 g / mol; Add an appropriate amount of SiO2 with an average particle size of 14 nm, heat to 120 °C, and stir until uniformly mixed to obtain a prepolymer melt; Pour the prepolymer melt onto a glass slide, heat to 120 °C in a vacuum chamber overnight, remove the generated film from the glass slide, weigh it, immerse the film in an ethyl acetate solution of lithium salt for 24 hours, after swelling, dry in a vacuum chamber at 60 °C overnight to form the first film, weigh it to calculate the amount of lithium salt; Transfer the first film to an argon-filled glove box to prevent the first film from absorbing moisture from the air, add propylene carbonate to the glove box, and after the first film swells for at least 2 hours and reaches equilibrium, obtain the polymer electrolyte membrane S15.
[0130] (2) Preparation of elastic polymer electrolyte composite positive electrode Take 35wt% lithium iron phosphate (LiFePO4), 5wt% single-walled carbon nanotubes, 45wt% polymer electrolyte membrane S15 and N-methylpyrrolidone (NMP), mix them evenly, pour the mixture onto a block of polytetrafluoroethylene, heat it under vacuum to 150℃, and leave it overnight to obtain the elastic polymer electrolyte composite positive electrode C15.
[0131] Example 16 (1) Preparation of elastic polymer electrolyte membrane The first monomer (bromonaphthyl diamino ether, NDIO, R1=R2=H, n1=m1=4), the second monomer (bromobispyrrole vinyl ether, R3=R4=H, n2=m2=4) and the third monomer (bromopyrrolopyrrole ether, R5=R6=H, n3=m3=4) are provided.
[0132] The first, second, and third monomers were mixed in a molar ratio of 5:3:2. The resulting mixture was heated in chlorobenzene solvent to 120°C to undergo a polymerization reaction, producing a polymer with a weight-average molecular weight of 1.6 × 10⁻⁶. 5 g / mol; Add an appropriate amount of SiO2 with an average particle size of 14 nm, heat to 120 °C, stir until uniformly mixed to obtain a prepolymer melt; Pour the prepolymer melt onto a glass slide, heat to 120 °C in a vacuum chamber overnight, remove the generated film from the glass slide, weigh it, immerse the film in an ethyl acetate solution of lithium salt for 24 hours, after swelling, dry in a vacuum chamber at 60 °C overnight to form the first film, weigh it to calculate the amount of lithium salt; Transfer the first film to an argon-filled glove box to prevent the first film from absorbing moisture from the air, add propylene carbonate to the glove box, and after the first film swells for at least 2 hours and reaches equilibrium, obtain the polymer electrolyte membrane S16.
[0133] (2) Preparation of elastic polymer electrolyte composite positive electrode Take 35wt% lithium iron phosphate (LiFePO4), 5wt% single-walled carbon nanotubes, 45wt% polymer electrolyte membrane S16 and N-methylpyrrolidone (NMP), mix them evenly, pour the mixture onto a block of polytetrafluoroethylene, heat it under vacuum to 150℃, and leave it overnight to obtain the elastic polymer electrolyte composite positive electrode C16.
[0134] Example 17 (1) Preparation of elastic polymer electrolyte membrane The first monomer (bromonaphthyl diamino ether, NDIO, R1=R2=H, n1=m1=4), the second monomer (bromobispyrrole vinyl ether, R3=R4=H, n2=m2=4) and the third monomer (bromopyrrolopyrrole ether, R5=R6=H, n3=m3=4) are provided.
[0135] The first, second, and third monomers were mixed in a molar ratio of 2:1:1. The resulting mixture was heated in chlorobenzene solvent to 120°C to undergo a polymerization reaction, producing a polymer with a weight-average molecular weight of 2.3 × 10⁻⁶. 5g / mol; Add an appropriate amount of SiO2 with an average particle size of 14 nm, heat to 120 °C, stir until uniformly mixed to obtain a prepolymer melt; Pour the prepolymer melt onto a glass slide, heat to 120 °C in a vacuum chamber overnight, remove the generated film from the glass slide, weigh it, immerse the film in an ethyl acetate solution of lithium salt for 24 hours, after swelling, dry overnight in a vacuum chamber at 60 °C to form the first film, weigh it to calculate the amount of lithium salt; Transfer the first film to an argon-filled glove box to prevent the first film from absorbing moisture from the air, add propylene carbonate to the glove box, and after the first film swells for at least 2 hours and reaches equilibrium, obtain the polymer electrolyte membrane S17.
[0136] (2) Preparation of elastic polymer electrolyte composite positive electrode Take 35 wt% lithium iron phosphate (LiFePO4), 5 wt% single-walled carbon nanotubes, 45 wt% polymer electrolyte membrane S17 and N-methylpyrrolidone (NMP), mix them evenly, pour the mixture onto a block of polytetrafluoroethylene, heat it under vacuum to 150°C, and leave it overnight to obtain the elastic polymer electrolyte composite positive electrode C17.
[0137] Example 18 (1) Preparation of elastic polymer electrolyte membrane The first monomer (bromonaphthyl diamino ether, NDIO, R1=R2=H, n1=m1=4), the second monomer (bromobispyrrole vinyl ether, R3=R4=H, n2=m2=4) and the third monomer (bromopyrrolopyrrole ether, R5=R6=H, n3=m3=4) are provided.
[0138] The first, second, and third monomers were mixed in a molar ratio of 4:3:1. The resulting mixture was heated in chlorobenzene solvent to 120°C to undergo a polymerization reaction, producing a polymer with a weight-average molecular weight of 2.2 × 10⁻⁶. 5 g / mol; Add an appropriate amount of SiO2 with an average particle size of 14 nm, heat to 120 °C, and stir until uniformly mixed to obtain a prepolymer melt; Pour the prepolymer melt onto a glass slide, heat to 120 °C in a vacuum chamber overnight, remove the generated film from the glass slide, weigh it, immerse the film in an ethyl acetate solution of lithium salt for 24 hours, after swelling, dry in a vacuum chamber at 60 °C overnight to form the first film, weigh it to calculate the amount of lithium salt; Transfer the first film to an argon-filled glove box to prevent the first film from absorbing moisture from the air, add propylene carbonate to the glove box, and after the first film swells for at least 2 hours and reaches equilibrium, obtain the polymer electrolyte membrane S18.
[0139] (2) Preparation of elastic polymer electrolyte composite positive electrode Take 35 wt% lithium iron phosphate (LiFePO4), 5 wt% single-walled carbon nanotubes, 45 wt% polymer electrolyte membrane S18 and N-methylpyrrolidone (NMP), mix them evenly, pour the mixture onto a block of polytetrafluoroethylene, heat it under vacuum to 150°C, and leave it overnight to obtain the elastic polymer electrolyte composite positive electrode C18.
[0140] Example 19 (1) Preparation of elastic polymer electrolyte membrane The first monomer (bromonaphthyl diamino ether, NDIO, R1=R2=H, n1=m1=4), the second monomer (bromobispyrrole vinyl ether, R3=R4=H, n2=m2=4) and the third monomer (bromopyrrolopyrrole ether, R5=R6=H, n3=m3=4) are provided.
[0141] The first, second, and third monomers were mixed in a molar ratio of 6:5:1. The resulting mixture was heated in chlorobenzene solvent to 120°C to undergo a polymerization reaction, producing a polymer with a weight-average molecular weight of 1.9 × 10⁻⁶. 5 g / mol; Add an appropriate amount of SiO2 with an average particle size of 14 nm, heat to 120 °C, stir until uniformly mixed to obtain a prepolymer melt; Pour the prepolymer melt onto a glass slide, heat to 120 °C in a vacuum chamber overnight, remove the generated film from the glass slide, weigh it, immerse the film in an ethyl acetate solution of lithium salt for 24 hours, after swelling, dry in a vacuum chamber at 60 °C overnight to form the first film, weigh it to calculate the amount of lithium salt; Transfer the first film to an argon-filled glove box to prevent the first film from absorbing moisture from the air, add propylene carbonate in the glove box, and after the first film swells for at least 2 hours and reaches equilibrium, obtain the polymer electrolyte membrane S19.
[0142] (2) Preparation of elastic polymer electrolyte composite positive electrode Take 35 wt% lithium iron phosphate (LiFePO4), 5 wt% single-walled carbon nanotubes, 45 wt% polymer electrolyte membrane S19 and N-methylpyrrolidone (NMP), mix them evenly, pour the mixture onto a block of polytetrafluoroethylene, heat it under vacuum to 150°C, and leave it overnight to obtain the elastic polymer electrolyte composite positive electrode C19.
[0143] To highlight the beneficial effects of this application, the following comparative examples are provided: Comparative Example 1 Take 0.683g of lithium salt (LiTFSI) and 1g of polyethylene oxide (PEO, weight average molecular weight of 400000g / mol), add them to an appropriate amount of anhydrous acetonitrile, stir at room temperature for 24 hours, cast into a film in polytetrafluoroethylene, and then vacuum dry at 50℃ for 48 hours to obtain polymer electrolyte RS1.
[0144] Comparative Example 2 (1) Preparation of elastic polymer electrolyte membrane A first monomer (bromonaphthalene diamino ether, NDIO, R1=R2=H, n1=m1=4) and a second monomer (bromobispyrrole vinyl ether, R3=R4=H, n2=m2=4) are provided. The first and second monomers are mixed in a 1:1 molar ratio. The resulting mixture is heated to 120°C in chlorobenzene solvent to undergo a polymerization reaction, producing a polymer with a weight-average molecular weight of 2.3 × 10⁻⁶. 5 g / mol; Add an appropriate amount of SiO2 with an average particle size of 14 nm, heat to 120 °C, and stir until uniformly mixed to obtain a prepolymer melt; Pour the prepolymer melt onto a glass slide, heat to 120 °C in a vacuum chamber overnight, remove the generated film from the glass slide, weigh it, immerse the film in an ethyl acetate solution of lithium salt for 24 hours, after swelling, dry in a vacuum chamber at 60 °C overnight to form the first film, weigh it to calculate the amount of lithium salt; Transfer the first film to an argon-filled glove box to prevent the first film from absorbing moisture from the air, add propylene carbonate to the glove box, and after the first film swells for at least 2 hours and reaches equilibrium, obtain the polymer electrolyte membrane RS2.
[0145] Comparative Example 3 (1) Preparation of elastic polymer electrolyte membrane The first monomer (bromonaphthyl diamino ether, NDIO, R1=R2=H, n1=m1=4) and the third monomer (bromopyrrolopyrrole ether, R5=R6=H, n3=m3=4) are provided.
[0146] The first and third monomers were mixed in a 1:1 molar ratio. The resulting mixture was heated in chlorobenzene solvent to 120°C to undergo a polymerization reaction, producing a polymer with a weight-average molecular weight of 2.6 × 10⁻⁶. 5 g / mol; Add an appropriate amount of SiO2 with an average particle size of 14 nm, heat to 120 °C, and stir until uniformly mixed to obtain a prepolymer melt; Pour the prepolymer melt onto a glass slide, heat to 120 °C in a vacuum chamber overnight, remove the generated film from the glass slide, weigh it, immerse the film in an ethyl acetate solution of lithium salt for 24 hours, after swelling, dry in a vacuum chamber at 60 °C overnight to form the first film, weigh it to calculate the amount of lithium salt; Transfer the first film to an argon-filled glove box to prevent the first film from absorbing moisture from the air, add propylene carbonate to the glove box, and after the first film swells for at least 2 hours and reaches equilibrium, obtain the polymer electrolyte membrane RS3.
[0147] To provide strong support for the effectiveness of the embodiments of this application, corresponding tests were conducted on the embodiments of this application and the comparative examples. The test content and methods are as follows: Thermogravimetric analysis: The instrument TAG-SDTA851 was used, with a heating rate of 20℃ / min, and the temperature was raised to 600℃ in a nitrogen atmosphere.
[0148] Crystallinity and glass transition temperature: Differential scanning calorimetry (DSC-Q2000) was used, calibrated with indium standards. Sample weights ranged from 8 mg to 10 mg, and the temperature range was -70 to 150 °C. Heating and cooling rates were both 10 °C / min. The crystallinity and glass transition temperature of polymer electrolyte film samples S1-S15 and RS1 were recorded.
[0149] Tensile strength and elongation at break: The tensile and compression testing equipment, Instron 5565, was used with a strain rate of 100% / min.
[0150] Electrochemical impedance spectroscopy: The test frequency is from 1mHz to 100mHz, and the temperature is adjusted using a constant temperature and humidity chamber with a temperature variation range of 20℃-80℃. The disturbance signal is 50mV.
[0151] Electrical conductivity: The polymer electrolyte membranes S1-S16 prepared in Examples 1-16 and RS1 of the comparative example were cut into pieces with an area of 2 cm². 2 A 0.4 mm thick polymer electrolyte membrane was sandwiched between two parallel stainless steel sheets inside a glove to assemble a 2032 coin cell. The cell model was "stainless steel sheet | polymer electrolyte membrane | stainless steel sheet". A CHI660B electrochemical workstation from Shanghai Chenhua Instruments Co., Ltd. was used. The test frequency range was 1 kHz to 100 kHz, and the temperature range was -20℃, -15℃, 20℃, 50℃, 80℃, and 110℃. The bulk resistance (Rh) of the polymer electrolyte was the intersection of the Nyquist curve and the real axis. The ionic conductivity was calculated according to the formula σ = I / (A·Rh), where σ is the ionic conductivity, I is the thickness of the elastic polymer electrolyte membrane, and A is the contact area between the elastic polymer electrolyte membrane and the electrode.
[0152] Electrochemical stability testing: A 2032 coin cell was assembled using an elastic polymer electrolyte in an argon-filled glove box. The cell model consisted of a lithium metal sheet, a polymer electrolyte membrane, and a stainless steel sheet. Cyclic voltammetry was used, with the voltage scan starting from the open-circuit voltage, decreasing to -0.7V, and then increasing to 5.5V at a rate of 1mV / s. The test results are shown in Table 1.
[0153] Table 1
[0154] As shown in Table 1, compared with the traditional electrolyte of Comparative Example 1, the electrolyte prepared using the polymer matrix provided by this invention has better ionic conductivity and lower electrochemical impedance, exhibiting excellent electrochemical performance. At the same time, it is superior to the traditional electrolyte of Comparative Example 1 in terms of mechanical properties such as elongation at break, tensile strength, and strain recovery rate, which can effectively improve the safety performance and service life of lithium-ion batteries.
Claims
1. A polymer electrolyte matrix, characterized in that, The polymer electrolyte matrix is composed of structural unit A1, structural unit A2 and structural unit A3. The structural formula of structural unit A1 is shown in formula (1-1), the structural formula of structural unit A2 is shown in formula (1-2), and the structural formula of structural unit A3 is shown in formula (1-3) or formula (1-4). (1-1) (1-2) (1-3) (1-4) In formulas (1-1), (1-2), (1-3), and (1-4), R1, R2, R3, R4, R5, R6, R7, and R8 are independently selected from H or alkyl groups; m1, m2, m3, m4, n1, n2, n3, and n4 are independently selected from integers from 1 to 100. Indicates the connection bit.
2. The polymer electrolyte matrix as described in claim 1, characterized in that, The weight-average molecular weight of the polymer electrolyte matrix is 1×10⁻⁶. 5 g / mol ~ 2 × 10 6 g / mol.
3. A method for preparing a polymer electrolyte matrix, characterized in that, Includes the following steps: The first conjugated monomer, the second conjugated monomer, and the third conjugated monomer are mixed and polymerized to obtain the polymer electrolyte matrix; the first conjugated monomer includes a halonaphthyl diamine ether as shown in formula (2-1); the second conjugated monomer includes a halobispyrrole vinyl ether as shown in formula (2-2); and the third conjugated monomer includes a halobispyrrole ether as shown in formula (2-3) or a halopyrrolopyrrole ether as shown in formula (2-4). (2-1) (2-2) (2-3) (2-4) In formulas (2-1), (2-2), (2-3), and (2-4), X is a halogen atom, R1, R2, R3, R4, R5, R6, R7, and R8 are independently selected from H or alkyl groups; m1, m2, m3, m4, n1, n2, n3, and n4 are independently selected from integers from 1 to 100.
4. The preparation method according to claim 3, characterized in that, The polymerization reaction temperature is 100℃~150℃.
5. A polymer electrolyte, characterized in that, It includes the polymer electrolyte matrix as described in claim 1 or 2 and the lithium salt dispersed in the polymer electrolyte matrix.
6. The polymer electrolyte as described in claim 5, characterized in that, The ratio of the number of lithium ions in the lithium salt to the number of oxygen atoms in the polymer electrolyte matrix is 1:(6~40).
7. The polymer electrolyte according to claim 5, characterized in that, The polymer electrolyte also includes inorganic fillers, and the mass ratio of the inorganic fillers to the polymer electrolyte matrix is 1:(14~30).
8. The polymer electrolyte as claimed in claim 5, characterized in that, The polymer electrolyte also includes a plasticizer, and the mass ratio of the plasticizer to the polymer electrolyte matrix is 1:(1~1.8).
9. The polymer electrolyte as described in claim 5, characterized in that, The polymer electrolyte has an ionic conductivity of 1×10⁻⁶. -6 S / cm ~ 1×10 -2 S / cm; the tensile strength of the polymer electrolyte is 0.2 MPa to 0.9 MPa.
10. A method for preparing a polymer electrolyte, characterized in that, include: The polymer electrolyte matrix as described in claim 1 or 2 is contacted with a lithium salt solution and dried to obtain the polymer electrolyte.
11. A battery electrode, characterized in that, It includes a current collector and an electrode material disposed on the current collector, the electrode material including an electrode active material and a polymer electrolyte matrix as described in claim 1 or 2.
12. A secondary battery, characterized in that, The secondary battery includes the polymer electrolyte matrix as described in claim 1 or 2; or the secondary battery includes the polymer electrolyte as described in any one of claims 5-9; or the secondary battery includes the battery electrode as described in claim 11.
13. An electronic device, characterized in that, The electronic device includes the secondary battery as described in claim 12.
Citation Information
Patent Citations
N-type conjugated polymer containing oligomeric ethylene glycol side chain modified naphthalene diimide unit and application of conjugated polymer in organic photoelectric devices
CN109021214A
Semiconductor materials prepared from bridged bithiazole copolymers
US20130144065A1